2018
DOI: 10.1007/s12325-018-0679-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Powered and Tissue-Specific Endoscopic Stapling Technology on Clinical and Economic Outcomes of Video-Assisted Thoracic Surgery Lobectomy Procedures: A Retrospective, Observational Study

Abstract: IntroductionVideo-assisted thoracic surgery (VATS) lung resections are complex procedures with a critical role played by endoscopic staplers in the transection of vessels, bronchi, and lung tissue. This retrospective, observational study compared hospital resource use, costs, and complications of VATS lobectomy procedures for whom powered versus manual endoscopic surgical staplers were used.MethodsPatients ≥ 18 years of age undergoing elective VATS lobectomy during an inpatient admission from January 1, 2012 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 19 publications
(28 reference statements)
2
32
0
Order By: Relevance
“…Powered endoscopic staplers reportedly lead to fewer bleeding events during pulmonary vessel transection than manual endoscopic staplers due to increased stability during firing. 3,4 Miller et al also found that powered staplers demonstrate superior results in reduced total hospital length of stay and total hospital cost in addition to bleeding management; however, this study was limited by differences in patient characteristics and different approaches in multiple centers and/or surgeons' experience, making it difficult to draw clear conclusions about the full benefits of powered versus manual staplers. 4 Our results, from a single center, demonstrate that tremors during firing may not be the leading cause of bleeding during vessel transection.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Powered endoscopic staplers reportedly lead to fewer bleeding events during pulmonary vessel transection than manual endoscopic staplers due to increased stability during firing. 3,4 Miller et al also found that powered staplers demonstrate superior results in reduced total hospital length of stay and total hospital cost in addition to bleeding management; however, this study was limited by differences in patient characteristics and different approaches in multiple centers and/or surgeons' experience, making it difficult to draw clear conclusions about the full benefits of powered versus manual staplers. 4 Our results, from a single center, demonstrate that tremors during firing may not be the leading cause of bleeding during vessel transection.…”
Section: Discussionmentioning
confidence: 87%
“…3,4 Miller et al also found that powered staplers demonstrate superior results in reduced total hospital length of stay and total hospital cost in addition to bleeding management; however, this study was limited by differences in patient characteristics and different approaches in multiple centers and/or surgeons' experience, making it difficult to draw clear conclusions about the full benefits of powered versus manual staplers. 4 Our results, from a single center, demonstrate that tremors during firing may not be the leading cause of bleeding during vessel transection. Differences in bleeding after stapling did not appear to be due to variation in staple characteristics or stapler anvil jaw angle, but rather loaded and closed anvil jaw gap; the closed anvil jaw gap for the loaded Endo-GIA TM iDrive TM stapler plus gray cartridge was up to six times smaller than that of the loaded ECHELON FLEX TM PVS.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The lower in-hospital hemostasis-related complications associated with Ethicon’s powered staplers is consistent with previously published findings in both bariatric and thoracic procedures. 2 , 3 , 5 , 8 However, while these earlier publications could not characterize such differences beyond the potential impact of powered firing (as they compared powered to manual stapling technologies), this analysis suggests that, potentially, there are additional differences between the stapling platforms that drive hemostasis-related complications. From an innovation perspective, although certain components of SIG are newer, the TriStaple TM cartridge reload remains the same as in Medtronic’s older manual stapling technology – potentially offering similar tissue effects as observed in the earlier studies.…”
Section: Discussionmentioning
confidence: 96%